2017
DOI: 10.1016/j.ab.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Red-emitting chimeric firefly luciferase for in vivo imaging in low ATP cellular environments

Abstract: Beetle luciferases have been adapted for live cell imaging where bioluminescence is dependent on the cellular availability of ATP, O 2 , and added luciferin. Previous Photinus pyralis red-emitting variants with high K m values for ATP have performed disappointingly in live cells despite having much higher relative specific activities than enzymes like Click Beetle Red (CBR). We engineered a luciferase variant PLR3 having a K m value similar to CBR and ~2.6-fold higher specific activity.The red-emitting PLR3 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…We show that CB is immunogenic in B6 mice and identify the immunodominant H-2D b -restricted CB 101-109 epitope. CB luciferases are commonly used for robust in vivo imaging in mice (Branchini et al, 2017;Hall et al, 2018;Serganova et al, 2016; (D) Proportion of total CD8+ T cells producing IFNg following ex vivo re-stimulation with CB 101-109 peptide at day 22. (E) Number of tetramer+ T cells producing IFNg at day 22.…”
Section: Discussionmentioning
confidence: 99%
“…We show that CB is immunogenic in B6 mice and identify the immunodominant H-2D b -restricted CB 101-109 epitope. CB luciferases are commonly used for robust in vivo imaging in mice (Branchini et al, 2017;Hall et al, 2018;Serganova et al, 2016; (D) Proportion of total CD8+ T cells producing IFNg following ex vivo re-stimulation with CB 101-109 peptide at day 22. (E) Number of tetramer+ T cells producing IFNg at day 22.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 10 , 11 For example, a recent study reported a chimeric luciferase that emits red light with a lower K m value for ATP. 12 Alternatively, instead of engineering the enzyme, synthetic luciferin substrates have been developed that improve cell permeability of the substrate to improve emission and alter the luminescence spectra of the emitted light. 13 15 Recombinant luciferases have also been used for applications in vitro, for example, as biosensors 16 and as the light source in bioluminescence resonance energy transfer reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For years ATP has been quantified by measuring the light produced by the firefly enzyme luciferase using a luminometer. The amount of light produced is directly proportional to the amount of ATP [ 17 , [19] , [20] , [21] ]. A common method employed to quantify ATP production is to isolate mitochondria and measure ATP using fluorometry [ 22 ].…”
Section: Discussionmentioning
confidence: 99%